Error Analysis of Dyscalculia Children in Solving the Basic Arithmetic Word Problems Student of Inclusion Class in an Elementary School - Qonita, Wilda (Sains Data Jurnal Studi Matematika dan Teknologi, 2024)
Dyscalculia is a form of learning difficulty experienced by children in mathematics learning that involves counting skills, that is learning disabilities that affect the ability of children to acquire arithmetic skills. Many elementary students have difficulty in solving word problems, especially students with mathematics learning difficulties. Solving a word problem is a common difficulty for students with learning disabilities, so a teacher needs to have a clear understanding of the specific errors made by students with learning disabilities during problem-solving. Errors in solving mathematical problems need to be analyzed to determine the types of errors. In this research the types of student errors in solving basic arithmetic word problems related to the topic of integers. The difficulty in mathematics learning can be identified by using Newman's Error Analysis (NEA). The error analysis will include errors in reading, comprehension, transformation, process skills, and encoding. This research is a descriptive qualitative nature that aims a describe the types of errors that dyscalculia children make in solving the basic arithmetic word problems. The subjects of the research were students from the fifth grade of inclusion class in an elementary school. Data collection techniques used in this research are written tests and interviews.